2014
DOI: 10.1016/j.neuron.2014.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Visual Stimulation Switches the Polarity of Excitatory Input to Starburst Amacrine Cells

Abstract: Summary Direction-selective ganglion cells (DSGCs) are tuned to motion in one direction. Starburst amacrine cells (SACs) are thought to mediate this direction selectivity through precise anatomical wiring to DSGCs. Nevertheless, we previously found that visual adaptation can reverse DSGCs’ directional tuning, overcoming the circuit anatomy. Here we explore the role of SACs in the generation and adaptation of direction selectivity. First, using pharmaco-genetics and two-photon calcium imaging, we validate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 60 publications
5
63
0
Order By: Relevance
“…Although direction-selective circuits in the retina have been studied in considerable detail (Borst and Euler 2011;Briggman et al 2011), how ambient illumination influences their function is not well understood. A pair of recent studies showed that DSGCs can switch the direction of their motion preference in response to repeated stimulation (Rivlin-Etzion et al 2012;Vlasits et al 2014). These changes in motion preference appear to be caused by shifts in the response polarity of starburst amacrine cells (SACs), critical interneurons presynaptic to DSGCs (Vlasits et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although direction-selective circuits in the retina have been studied in considerable detail (Borst and Euler 2011;Briggman et al 2011), how ambient illumination influences their function is not well understood. A pair of recent studies showed that DSGCs can switch the direction of their motion preference in response to repeated stimulation (Rivlin-Etzion et al 2012;Vlasits et al 2014). These changes in motion preference appear to be caused by shifts in the response polarity of starburst amacrine cells (SACs), critical interneurons presynaptic to DSGCs (Vlasits et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A pair of recent studies showed that DSGCs can switch the direction of their motion preference in response to repeated stimulation (Rivlin-Etzion et al 2012;Vlasits et al 2014). These changes in motion preference appear to be caused by shifts in the response polarity of starburst amacrine cells (SACs), critical interneurons presynaptic to DSGCs (Vlasits et al 2014). Unlike the changes in contrast preference observed in this study, SAC responses were converted gradually and irreversibly by preferential stimulation of receptive field centers (circle: ϳ225-m diameter) with bright light (100,000 R*) causing shifts in the balance of rod/centerand cone/surround-driven signals (Vlasits et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This imaging technique has proven to be quite powerful in characterizing the receptive field properties of retinal ganglion cells [9][10][11][12]. We loaded retinas of WT mice near eye-opening (P13-P14) and in adulthood (>P30) with the calcium dye Oregon green 488 BAPTA-1 hexapotassium salt (OGB-1) via electroporation, thus uniformly labeling the ganglion cell layer ( Figure 1A; see Supplemental Information).…”
Section: Clustering Of Dsgc Preferred Directions Along Cardinal Axesmentioning
confidence: 99%